Performance Analysis With Wireless Lan Networks Using The Quality Of Service Method - Wahyudi, Anggy; Hadi, Aulia Fitrul; Sovia, Rini (Universitas Andalas, 2020)
The use of the internet currently has very high mobility, both used for streaming, browsing, downloading and uploading data. Along with the changing times and the demands for information services that are fast, precise, and accurate, making the network a major need, especially in the world of education. The use of internet facilities requires management to manage each data. For this reason, there is a need for Quality of Service on the network to optimize the distribution of networks evenly and fairly for each client and network user. The results of the study show that network quality by implementing Quality of Service is more optimal and network distribution is more even and stable